1983
DOI: 10.1002/mpo.2950110510
|View full text |Cite
|
Sign up to set email alerts
|

Can hypertransfusion attenuate myelosuppression associated with combination chemotherapy in patients with inoperable bronchogenic carcinoma? A report of a randomised, controlled study

Abstract: Based on the concept of "stem-cell competition," hypertransfusion has been shown to attenuate the leucopenia associated with chemotherapy in children with leukemia. We conducted a randomized, controlled study of hypertransfusion in 25 patients with inoperable lung cancer who received combination chemotherapy consisting of methotrexate, adriamycin, cyclophosphamide, and CCNU (Lomustine) (MACC scheme). Twelve patients in the hypertransfusion group were given red cell transfusion to a hemoglobin value greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Other potential benefits may include more rapid neutrophil and PLT recovery, improved functional status, and improved quality of life. [50][51][52][53][54][55][56][57][58][59][60][61] In addition, a high pretransplant Hb level has been demonstrated to be associated with improved survival. 62 In contrast, there is evidence that, in certain patient populations, RBC transfusion may be associated with decreased early or long-term survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential benefits may include more rapid neutrophil and PLT recovery, improved functional status, and improved quality of life. [50][51][52][53][54][55][56][57][58][59][60][61] In addition, a high pretransplant Hb level has been demonstrated to be associated with improved survival. 62 In contrast, there is evidence that, in certain patient populations, RBC transfusion may be associated with decreased early or long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Based on experimental animal studies, 11 we have hypothesized that this effect may be especially important in patients with thrombocytopenia including patients with AML receiving induction chemotherapy and patients undergoing SCT. Other potential benefits may include more rapid neutrophil and PLT recovery, improved functional status, and improved quality of life 50‐61 . In addition, a high pretransplant Hb level has been demonstrated to be associated with improved survival 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the past century suggested that RBC transfusion could accelerate haematopoietic recovery in children with leukaemia [31,32]. There is also evidence that RBC transfusion attenuates chemotherapy‐induced myelosuppression in adults [33]. Although these studies used hypertransfusion with RBC concentrates aiming Hb levels of 16 g/dl and higher, we wanted to analyse whether different RBC transfusion rates had impact on CR rates or time to discharge from hospital (both depending on haematopoietic recovery).…”
Section: Discussionmentioning
confidence: 99%